Pengaruh Brand Association, Brand Reliability, Dan Brand Intention Terhadap Brand Loyalty: Studi Kasus Pada Indihome Kota Bogor - Wibisono, Sandy; Clarita, Teresa; Sulistiono, Sulistiono (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to determine whether Brand Association, Brand Reliability, and Brand Intention have a partial and simultaneous effect on Brand Loyalty. The population in this study are consumers who have used Indihome in the city of Bogor with a total sample of 150 people. The sampling method used is a non-random sampling method. The data analysis method used is multiple linear regression analysis to determine the effect of Brand Association, Brand Reliability, and Brand Intention on Brand Loyalty. Data testing was performed using IBM SPSS Statistics 24 Software. The results of this study are as follows: (1) Brand Association partially affects Brand Loyalty with a t-count value greater than t table (3.333> 1.65). (2) Brand Reliability partially affects Brand Loyalty with the t value greater than t table (2.709> 1.65). (3) Brand Intention partially affects Brand Loyalty with the value of t count greater than t table (4.565> 1.65). (4) Brand Association, Brand Reliability, and Brand Intention simultaneously have a positive and significant effect on Brand Loyalty with a calculated F value greater than F table (122.265> 2.67) and a significance value of 0.000. (5) The three independent variables (Brand Association, Brand Reliability, and Brand Intention) are able to explain variations in the dependent variable (Brand Loyalty) by 72%, while 28% Brand Loyalty is influenced by other independent variables. Keywords: Brand Association, Brand Reliability, Brand Intention, and Brand Loyalty